Mechanoregulation of Vascular Endothelial Growth Factor Receptor 2 in Angiogenesis - Miller, Bronte; Sewell-Loftin, Mary Kathryn (Frontiers in Cardiovascular Medicine, 2022)
The endothelial cells that compose the vascular system in the body display a wide range of mechanotransductive behaviors and responses to biomechanical stimuli, which act in concert to control overall blood vessel structure and function. Such mechanosensitive activities allow blood vessels to constrict, dilate, grow, or remodel as needed during development as well as normal physiological functions, and the same processes can be dysregulated in various disease states. Mechanotransduction represents cellular responses to mechanical forces, translating such factors into chemical or electrical signals which alter the activation of various cell signaling pathways. Understanding how biomechanical forces drive vascular growth in healthy and diseased tissues could create new therapeutic strategies that would either enhance or halt these processes to assist with treatments of different diseases. In the cardiovascular system, new blood vessel formation from preexisting vasculature, in a process known as angiogenesis, is driven by vascular endothelial growth factor (VEGF) binding to VEGF receptor 2 (VEGFR-2) which promotes blood vessel development. However, physical forces such as shear stress, matrix stiffness, and interstitial flow are also major drivers and effectors of angiogenesis, and new research suggests that mechanical forces may regulate VEGFR-2 phosphorylation. In fact, VEGFR-2 activation has been linked to known mechanobiological agents including ERK/MAPK, c-Src, Rho/ROCK, and YAP/TAZ. In vascular disease states, endothelial cells can be subjected to altered mechanical stimuli which affect the pathways that control angiogenesis. Both normalizing and arresting angiogenesis associated with tumor growth have been strategies for anti-cancer treatments. In the field of regenerative medicine, harnessing biomechanical regulation of angiogenesis could enhance vascularization strategies for treating a variety of cardiovascular diseases, including ischemia or permit development of novel tissue engineering scaffolds. This review will focus on the impact of VEGFR-2 mechanosignaling in endothelial cells (ECs) and its interaction with other mechanotransductive pathways, as well as presenting a discussion on the relationship between VEGFR-2 activation and biomechanical forces in the extracellular matrix (ECM) that can help treat diseases with dysfunctional vascular growth.